2023
DOI: 10.3389/fonc.2023.1142017
|View full text |Cite
|
Sign up to set email alerts
|

GHRL as a prognostic biomarker correlated with immune infiltrates and progression of precancerous lesions in gastric cancer

Abstract: ObjectiveGhrelin is a protein that regulate appetite and energy balance in the human body, which is encoded by the ghrelin prepropeptide gene (GHRL). GHRL is linked with carcinogenesis and immune regulation. However, the correlation of GHRL to prognosis and tumor-infiltrating lymphocytes in gastric cancer (GC) remains unclear.MethodsIn this study, we assessed the transcriptional expression, prognosis, and different clinicopathological features about GHRL and the correlation between GHRL and tumor infiltration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 54 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…It may promote tumour progression by enhancing gastric adenocarcinoma cell proliferation, inhibiting apoptosis and promoting angiogenesis. 25 , 26 STC1 (Stanniocalcin 1) is a protein that is highly expressed in gastric adenocarcinoma. It may influence the malignant transformation of tumours by promoting the growth, invasion and metastasis of gastric adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may promote tumour progression by enhancing gastric adenocarcinoma cell proliferation, inhibiting apoptosis and promoting angiogenesis. 25 , 26 STC1 (Stanniocalcin 1) is a protein that is highly expressed in gastric adenocarcinoma. It may influence the malignant transformation of tumours by promoting the growth, invasion and metastasis of gastric adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…GHRL (Ghrelin) is a hormone that is highly expressed in gastric adenocarcinoma and is involved in tumour development by binding to its receptor, GHSR. It may promote tumour progression by enhancing gastric adenocarcinoma cell proliferation, inhibiting apoptosis and promoting angiogenesis 25,26 . STC1 (Stanniocalcin 1) is a protein that is highly expressed in gastric adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to that in normal tissues, the expression level of ghrelin in the tumor tissues of gastric cancer patients is significantly lower [90,91]. Studies have also observed that the expression of ghrelin in gastric adenocarcinoma cells is almost negligible [92].…”
Section: Ghrelin and Gastric Cancermentioning
confidence: 96%
“…Moreover, overexpressed MAT2A elevated the expression of RIP1 by increasing the H3K4 methylation at its promoter regions to induce the polarisation of M2 TAMs 47 . Several studies have demonstrated that the high expression of TUBA1A, ELK3, GKN2, COL1A2, RAI14, KIF23, GHRL, KCND2, SERPINE1, COL5A2, ALDOC and SLC38A2 and low expression of CD155 and AKR1B10 in GC indicate higher M2 TAM infiltration in the TME using data from public databases 93–107 . Furthermore, TAMs elevated the expression of PI3K‐γ by increasing the uptake of extracellular lipids, thereby inducing M2 phenotype polarisation 44 .…”
Section: The Role and Mechanism Of Tams In Gcmentioning
confidence: 99%
“… 47 Several studies have demonstrated that the high expression of TUBA1A, ELK3, GKN2, COL1A2, RAI14, KIF23, GHRL, KCND2, SERPINE1, COL5A2, ALDOC and SLC38A2 and low expression of CD155 and AKR1B10 in GC indicate higher M2 TAM infiltration in the TME using data from public databases. 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 Furthermore, TAMs elevated the expression of PI3K‐γ by increasing the uptake of extracellular lipids, thereby inducing M2 phenotype polarisation. 44 GC cells are characterised by enhanced glycolysis, producing large amounts of lactic acid that can induce the polarisation of M2 TAMs by activating the monocarboxylate channel transporter‐hypoxia inducible factor 1 subunit alpha (MCT–HIF1α) axis in macrophages.…”
Section: The Role and Mechanism Of Tams In Gcmentioning
confidence: 99%